Strategy as Practice in the Structurationist Perspective: What it is and why it is? : Toward an Ontology of Practice of Strategy in Organizations - Marietto, Marcio Luiz; Ribeiro, Ivano; Serra, Fernando Antonio Ribeiro (Ágora : revista de divulgação científica, 2016)
As a developing approach, Strategy as Practice appropriates other theories with converging ontological and epistemological assumptions to build its analytical body. Therefore, in this discipline the designs of Structurationism and the Historical-Cultural Activity Theory generally serve as the analytical basis, even though other theories such as Critical Realism, Sensemaking and Bourdieu’s concept of Habitus are alternative and/or complementary theories for the basic frameworks. This theoretical study offers a discussion on the appropriation of Structurationism that serves as one of the analytical theoretical structures of Strategy as Practice. The analytical procedure is guided by the central goal of discussing the ontological assumptions of Structurationism that support this perspective under the aegis of Strategy as Practice in the field of Organizational Strategy. For this purpose, the specific objectives are: a) to conduct a theoretical (albeit not exhaustive) review of Strategy as Practice; and b) to conduct a review of Giddens’ Theory of Structuration, followed by c) to offer a discussion on the theoretical/analytical specifics that Structurationism shown in studies of Strategy as Practice. The conclusion of the discussion shows adequate ontological agreement with the Structurationist assumptions adopted by the Strategy as Practice discipline, i.e., there is here a parallel intention to reveal an Ontology of Practice of Strategy in Organizations.